2011
DOI: 10.1016/j.virol.2011.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of HPV16 E6 protein by PDZ proteins, and potential implications for genome maintenance

Abstract: The E6 protein from high-risk human papillomaviruses appears necessary for persistence of viral episomes in cells but the underlying mechanism is unclear. E6 has many activities, including its ability to bind and degrade PDZ domain-containing proteins, such as hScrib. However little is known about the role of these interactions for E6 function and the viral life cycle. We now show that the levels of expression of wild-type E6 are increased in the presence of hScrib whilst a mutant E6 protein lacking the PDZ-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
54
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 41 publications
7
54
1
1
Order By: Relevance
“…A recent report showed that E6 with the PDZ motif deleted is unstable and that E6 association with PDZ domain proteins such as SCRIB increased E6 expression (31). Those results were obtained in transient-expression experiments, and the E6⌬PBM mutant employed in that study deleted 4 amino acids from the C terminus of E6.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…A recent report showed that E6 with the PDZ motif deleted is unstable and that E6 association with PDZ domain proteins such as SCRIB increased E6 expression (31). Those results were obtained in transient-expression experiments, and the E6⌬PBM mutant employed in that study deleted 4 amino acids from the C terminus of E6.…”
mentioning
confidence: 85%
“…In addition to primary keratinocytes, a nontransformed keratinocyte cell line termed NIKS can also maintain transfected alpha genus HPV DNA as episomes in prolonged culture; NIKS cells are of near-normal gross karyotype, are feeder cell and growth factor dependent, produce normal appearing squamous epithelium, and support the full HPV life cycle (28)(29)(30). In NIKS cells, deletion of the HPV-16 E6 PBM leads to the loss of genome maintenance (31).…”
mentioning
confidence: 99%
“…The E6 oncoproteins of high-risk HPV types have a C-terminal PDZ-binding motif (PBM) that is important for a normal viral life cycle and progeny production (for a review, see reference 3). PBM deletion causes viral genome integration, loss of replicative competence, and an increased potential for oncogenic transformation (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The presence of a PBM on the carboxy termini of cancer-causing E6 oncoproteins is essential for the viral life cycle (17)(18)(19)(20)(21) and contributes toward cell transformation (8,13) and the induction of malignancy (15,16). While it has been known for some time that this region of E6 could be phosphorylated, which, in turn, would be expected to inhibit E6-PDZ interactions (23,25), it has only recently become clear that this phosphorylation also confers upon E6 the ability to interact with 14-3-3 family members (23).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this region of E6 in the context of the whole viral genome result in marked defects to the viral life cycle, with reduced rates of viral DNA replication and a reduction in the expansion of replicationcompetent cells in the basal layers of the organotypic cultures (17,18). Furthermore, such viral genomes appear unstable over time, with rapid loss of viral episomes upon continued passaging of the cells (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%